Identification of a linear B-cell epitope on the “puff” loop of the Senecavirus A VP2 protein involved in receptor binding - Zhou, Hanrong; Sun, Mingxia; Su, Shibo; Meng, Liang; Yang, Wei; Yang, Lan; Shi, Xinqi; Li, Xin; Wang, Haiwei; Ma, Hongwei; Cai, Xuehui; Tang, Yan-Dong; et al. (Frontiers in Microbiology, 2024)
Senecavirus A (SVA) is an important emerging swine pathogen that causes vesicular lesions in swine and acute death in newborn piglets. VP2 plays a significant role in the production of antibodies, which can be used in development of diagnostic tools and vaccines. Herein, the aim of the current study was to identify B-cell epitopes (BCEs) of SVA for generation of epitope-based SVA marker vaccine. Three monoclonal antibodies (mAbs), named 2E4, 1B8, and 2C7, against the SVA VP2 protein were obtained, and two novel linear BCEs, 177 SLGTYYR 183 and 266 SPYFNGL 272 , were identified by peptide scanning. The epitope 177 SLGTYYR 183 was recognized by the mAb 1B8 and was fully exposed on the VP2 surface, and alanine scanning analysis revealed that it contained a high continuity of key amino acids. Importantly, we confirmed that 177 SLGTYYR 183 locates on "the puff" region within the VP2 EF loop, and contains three key amino acid residues involved in receptor binding. Moreover, a single mutation, Y182A, blocked the interaction of the mutant virus with the mAb 1B8, indicating that this mutation is the pivotal point for antibody recognition. In summary, the BCEs that identified in this study could be used to develop diagnostic tools and an epitope-based SVA marker vaccine.